Emotion Recognition from Text using LSTM algorithm - Preethi, V; Jadav, Nimisha; Shirsat, Komal; Bonde, Mohan (International Journal of Computer Sciences and Engineering, 2020)
The growth of social networking sites lead to increase in number of users and the amount of time spent by the users on these sites. In this era of internet, human expresses their emotions, sentiments and feelings via text, comments or tweets. People share their thoughts, feelings, experiences and opinions according to their observation and understanding. Emotion is an appearance of human behavior and plays an important role in human computer interaction. To extract the emotion behind this textual data we have proposed a model, emotion recognition from text. Our method detects emotion from a text-input by using deep learning algorithm Long Short Term Memory (LSTM). Emotions such as anger, love, surprise, joy, sadness and fear are classified through this model and the accuracy of each classifier is calculated.